Tingkat Kreativitas Siswa dalam Memecahkan Masalah Matematika Divergen Ditinjau dari Gaya Belajar Siswa - Hardiani Hardiani (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The aims of this research is to describe the level of Junior High School students’ creativity in solving divergent mathematical problem viewed from the students’ learning style. This study was qualitative descriptive reasearch. The subject of this research was 9 students from the ninth grade of MTs DDI Ujung Lero consisting of 4 students had visual learning style, 3 students had auditorial learning style, and 2 students had kinesthetic learning style. The researcher used purposive sampling and snowball method to select the subject. In collecting data, the researcher used grouping test in learning style, problem solving test of divergent mathematics, and interview. To techniques of data analysis in this research were as follows: (1) reducing data, (2) present of data in narrative text, (3) to conclude the level of students’ creativity at each learning style. The validity of data used time triangulation. Based on the research result, there are two findings as follows: main findings and other findings. The main findings shows that (1) the students with visual and auditorial learning styles can eligible to indicators of creativity, fluently and flexibility, so that those students have the third level of creativity (creative) in solving divergent mathematical problem, (2) while, the students with kinesthetic learning style can eligible to indicators of creativity, namely fluently. So that those students have the first level of creativity (less creative) in solving divergent mathematical problem. Then, the other findings data shows that (1) there are two students with visual learning style are identified having the second level (quite creative) and the forth level (very creative) of creativity in solving divergent mathematical problem, (2) while there is one student with auditorial learning style is identified not creative (level 0). Based on the findings, it can be concluded that the students’ learning styles affect to students’ creativity, so that the teacher should know and understand students’ learning style in order to determine the best method of learning process. It is because each learning style affects to students’ different responses in getting the information.